Crystal structure and Hirshfeld surface analysis of methyl 1-(2,4-dichlorobenzyl)-5-methyl-1H-pyrazole-3-carboxylate - Aydin, Abdullah; Akkurt, Mehmet; Gur, Zehra Tugce; Banoglu, Erden (European Journal of Chemistry, 2018)
The title compound, C13H12Cl2N2O2, crystallizes with six molecules in the asymmetric unit, such that, the 1H-pyrazole rings are essentially planar. The six molecules are stabilized by intramolecular C-H···N and C-H···Cl interactions and the crystal structure is stabilized by intermolecular C-H···O hydrogen bonds, forming molecular sheets into paralel to the (-1 1 0) plane. These sheets are connected to each other by C-H···O hydrogen bonds and C-H···π interactions. In the Hirshfeld surface analysis, the H···H, Cl···H/H···Cl, C···H/H···C, O···H/H···O, N···H/H···N, Cl···Cl, Cl···O/O···Cl interactions add to 95.8% of the intermolecular contacts of the Hirshfeld surface area. The remaining contributions (2.9%) correspond to Cl···C/C···Cl, C···O/O···C, O···O and N···N interactions. Crystal Data for C13H12Cl2N2O2 (M = 299.15 g/mol): Triclinic, space group P-1 (no. 2), a = 12.0505(10) Å, b = 12.3189(11) Å, c = 29.184(3) Å, α = 88.565(4)°, β = 89.296(4)°, γ = 76.833(4)°, V = 4217.0(7) Å3, Z = 12, T = 296(2) K, μ(MoKα) = 0.460 mm-1, Dcalc = 1.414 g/cm3, 83073 reflections measured (2.8° ≤ 2Θ ≤ 47°), 12426 unique (Rint = 0.0411, Rsigma = 0.0235) which were used in all calculations. The final R1 was 0.0662 (I > 2σ(I)) and wR2 was 0.2481 (all data).
Keywords: 3. Good health